A Standardized Critical Size Defect Model in Normal and Osteoporotic Rats to Evaluate Bone Tissue Engineered Constructs. (11th March 2014) - Poser, Livia; Matthys, Romano; Schawalder, Peter; Pearce, Simon; Alini, Mauro; Zeiter, Stephan
Abstract : Tissue engineered constructs should be tested for their efficacy not only in normal but also in osteoporotic bone. The rat is an established animal model for osteoporosis and is used often for bone healing studies. In this study a defined and standardized critical size defect model in the rat suitable for screening new tissue engineered constructs in normal and osteoporotic bone is described and validated. Normal and ovariectomised Wistar rats received a unilateral middiaphyseal 5 mm defect in the femur, which was instrumented with a radiolucent PEEK plate fixed with angular stable titanium screws and left untreated. All animals were euthanized eight weeks after defect surgery and the bone healing was evaluated using radiographs, computed tomography measurements, and histology. The developed fixation system provided good stability, even in osteoporotic bone. The implants and ancillary instruments ensured consistent and facile placement of the PEEK plates. The untreated defects did not heal without intervention making the model a well-defined and standardized critical size defect model highly useful for evaluating tissue engineered solutions in normal and osteoporotic bone.